Behavioral Neurogenetics - Cryan, John F.; Reif, Andreas; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
The field of behavioral neurogenetics has developed significantly over the past two decades. This has been largely driven by technical advances in the field of molecular genetics both in model systems and in clinical analysis. Indeed, it is hoped that the elucidation and ongoing functionalisation of the human genome may provide new insights into the aetiology, course and, ultimately, treatment of psychiatric illnesses. This book covers a wide array of topics relevant to behavioral genetics from both a preclinical and clinical standpoint. Indeed in juxtaposing both areas of research the reader will appreciate the true translational nature of the field. Topics covered range from technical advances in genetic analysis in humans and animals to specific descriptions of advances in schizophrenia, attention disorders, depression and anxiety disorders, autism, aggression, neurodegeneration and neurodevelopmental disorders. The importance of gene-environment interactions is emphasised and the role of neuroimaging in unravelling the functional consequences of genetic variability described. This volume will be valued by both the basic scientist and clinician alike who may use it as a detailed reference book. It will also be of use to the novice to the field, to whom it will serve as an in-depth introduction to this exciting area of research.
Preface -- Part I. Preclinical Behavioral Genetics -- Part II. Clinical Behavioral Genetics.
Keywords: Medicine; Human genetics; Neurosciences; Psychiatry; Psychopharmacology; Animal behavior; Biomedicine; Neurosciences; Psychiatry; Psychopharmacology; Behavioural Sciences; Human Genetics; Molecular Medicine